Absence from Work of the Self-Employed: A Comparison with Paid Employees - Daniel S. J. Lechmann; Claus Schnabel (Institute for the Study of Labor (IZA), 2013)
Utilising a large representative data set for Germany, this study contrasts absenteeism of self-employed individuals and paid employees. We find that absence from work is clearly less prevalent among the self-employed than among paid employees. Only to a small extent, this difference can be traced back to differences in health status and job satisfaction. Furthermore, the gap in absenteeism is apparently not driven by different behaviour in case of sickness as we find no difference in the prevalence of presenteeism between the two groups. We suspect that different behaviour in case of healthiness plays a role, highlighting potential shirking and moral hazard problems in paid employment.
Keywords: I19; J22; J23; 330; absenteeism; Germany; self-employed; sick leave